PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KEMENTERIAN PEMUDA DAN OLAH RAGA REPUBLIK INDONESIA JAKARTA - Andriansyah, Zaenun; Suhartono, Irwan (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the influence of work motivation and discipline, both partially and simultaneously, on employee performance at the Ministry of Youth and Sports of the Republic of Indonesia, Jakarta. The research method that the author uses is a descriptive quantitative method and uses Multiple Linear Regression. The research was conducted on employees of the Ministry of Youth and Sports of the Republic of Indonesia, Jakarta. The sampling technique used a saturated sample of 70 respondents. Based on the research results showing partial results (t test), it was concluded that motivation (X1) had a significant effect on employee performance (Y) with a calculated t value of 3.742 > t table 1.667, reinforced with a significance level of 0.000 < 0.05. And work discipline (X2) has a significant effect on employee performance with a calculated t value of 6.530 > t table 1.667, reinforced with a significance level of 0.000 < 0.05. Meanwhile, based on the simultaneous regression test (F Test), the variabels motivation (X1) and work discipline (X2) have a positive and significant effect on employee performance (Y). The calculated F value > F table or (175.592 > 3.134) was obtained. This was also confirmed by the significance < 0.05 or (0.000 < 0.05).